Impact of Biochar Addition on Biofloc Nitrifying Bacteria and Inorganic Nitrogen Dynamics in an Intensive Aquaculture System of Shrimp - Wujie Xu; Demin Zhang; Haochang Su; Yu Xu; Xiaojuan Hu; Guoliang Wen; Yucheng Cao (Microorganisms)
In this study, an eight-week culture trial of Penaeus vannamei juveniles was conducted in commercial intensive systems to compare the impacts of biochar and molasses addition on biofloc nitrifying bacteria and inorganic nitrogen dynamics under limited water exchange conditions. During the trial, the biofloc concentration (in terms of VSS and TSS), quantities of total bacteria (TB) and total Vibrio (TV), and ratio of TV/TB in the culture water were lower in the biochar group compared to the molasses group. Metagenomic sequencing analysis revealed that the bacterial community composition of bioflocs showed higher α-diversity and complexity in the biochar group compared to the molasses group. Moreover, the abundance of nitrifying bacterial genera and functional genes in bioflocs was higher in the biochar group compared to the molasses group. Inorganic nitrogen dynamics showed that NH4+-N and NO2−-N were better controlled in the biochar group compared to the molasses group, as reflected by lower peaks of NH4+-N and NO2−-N and higher NO3−-N concentrations. Excellent production performance of shrimp was achieved, which in turn proved the reliable effect of biochar addition on the mediation of inorganic nitrogen transformation through nitrifying bacteria. These results showed that biochar addition could promote biofloc nitrifying bacteria and nitrification to more effectively control harmful nitrogen for shrimp efficient production. This study provides a practical example for the biochar application in biofloc-based systems for intensive aquaculture.